Toripalimab plus chemotherapy in the treatment of metastatic triple-negative breast cancer: a cost-effectiveness analysis - Cai, Hongfu; Huang, Lisheng; Zheng, Zhiwei (Frontiers in Public Health, 2024)
Objective: This study focuses on assessing the cost-effectiveness of incorporating toripalimab alongside chemotherapy for the treatment of patients diagnosed with metastatic triple-negative breast cancer from the perspective of the Chinese healthcare system. Methods: A partitioned survival model was constructed to simulate the costs and health outcomes over the lifetime of patients with mTNBC. Clinical data regarding overall survival, progression-free survival, and treatment-related adverse events were derived from the TORCHLIGHT clinical trials. Incremental cost-effectiveness ratio (ICER) were calculated based on the gains in quality-adjusted life-year (QALY). The willingness-to-pay (WTP) threshold was defined as 39,855.79 per QALY. Additionally, sensitivity analyses were conducted to examine the robustness of the model. Results: The total cost incurred by the group receiving toripalimab was 38,040.62,while the placebo plus chemotherapy was 26,102.07.The utilization of the toripalimab regimen resulted in an increase of 0.74 QALYs and an incremental cost of 11,938.55 compared to the placebo plus chemotherapy group. The ICER was 16133.18/QALY, indicating that toripalimab plus chemotherapy is a cost-effective strategy according to the WTP threshold. Sensitivity analyses confirmed the robustness of the results. Conclusion: This study suggests that the addition of toripalimab to chemotherapy for the treatment of mTNBC is a cost-effective strategy. The findings provide valuable evidence to guide decision-making regarding treatment selection for patients with mTNBC in China.